Paparan Etnik Melayu Sarawak Dalam Akhbar Tempatan - Siti Zanariah, Ahmad Ishak; Siti Haslina, Hussin; Malia, Taibi; Khadijah, Mohamad Tuah; Awang Ideris, Awg Daud (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Working Paper No. 73, September 2014